PENGARUH AKTIVA PRODUKTIF, DANA PIHAK KETIGA DAN LETAK GEOGRAFIS TERHADAP KINERJA OPERASIONAL LPD DI KECAMATAN TABANAN - Kusumayanti, Adek Devi; Jati, I Ketut (E-Jurnal Akuntansi, 2014)
This study aims to impact the growth in earning assets, deposits and geographical location on the operational performance of the LPD in the district of Tabanan 2008-2011. Of the 13 LPD, LPD obtained a sample of 10 studies using non-probability sampling method is purposive sampling method is the determination of the sample based on certain criteria. The test of data analysis is simultaneous regression and partial and multiple linear regression using dummy variables 1. The test results simultaneously (F test) it is known that the growth of earning assets, deposits and significant effect on the geographic location of the LPD ROA ratio in the district of Tabanan 2008-2011. Based on the t test showed that only credit growth and deposit growth which significantly influence the ROA ratio while deposits and geographical location has no effect on the LPD ROA ratio in the district of Tabanan 2008-2011.
Keywords: assets, deposits, geographic location, operational performance